Inflation persistence in the UK 1993-2019: From months to years - Huw Dixon; Yiyi Li; David Meenagh; Maoshan Tian (Cardiff University, Cardiff Business School, 2024)
In this paper we model monthly UK inflation and find that there is some small but significant autocorrelation, particularly at 12 months. We find that this autocorrelation in monthly inflation leads to significant persistence in the headline annual inflation figure. A one-off shock to monthly inflation will have an effect on the headline figure equal to 10% of the original shock after 24 months. We find that this 12-month effect is also present in most of the different types of expenditure. We also find that the 12-month effect is present when we introduce a variety of other demand and cost variables. We also look at core inflation (excluding food and energy) across 9 large market economies (including the USA, Germany, Japan and UK) and find that the 12-month effect is significant in all of them.
Keywords: E17; E31; E71; 330; inflation; persistence; UK; CPI